2021
DOI: 10.1021/acs.est.0c05777
|View full text |Cite
|
Sign up to set email alerts
|

Comammox Nitrospira Species Dominate in an Efficient Partial Nitrification–Anammox Bioreactor for Treating Ammonium at Low Loadings

Abstract: Bacteria capable of complete ammonia oxidation (comammox) are widespread and contribute to nitrification in wastewater treatment facilities. However, their roles in partial nitrification–anaerobic ammonium oxidation (anammox) systems remain unclear. In this study, a bench-scale bioreactor with continuous stirring was operated for more than 1000 days with limited oxygen supply to achieve efficient nitrogen removal (70.1 ± 2.7%) at a low ammonium loading of 35.2 mg-N/L/day. High-throughput amplicon sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 59 publications
1
65
0
1
Order By: Relevance
“…As one of the well‐known NOB genera, Nitrospira has been widely reported as a complete aerobic ammonia‐oxidizing bacteria (comammox) (Gonzalez‐Martinez et al, 2016; Lawson & Lücker, 2018), and some Nitrospira , such as Nitrospira inopinata , have a relatively low affinity for nitrite, making the symbiotic association with anammox bacteria possible. Sustained nitrogen loss has been observed in a combination of Comammox Nitrospira and anammox bacteria, especially in low ammonia condition and sometimes in low DO condition (Gottshall et al, 2020; Roots et al, 2019; Shao & Wu, 2021). The dominant NOB genus in this case, as shown in the reference (Yuan et al, 2020), was Nitrospira , and its relative abundance in the suspended solids was 2 times higher in summer and 7 times higher in winter than the biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the well‐known NOB genera, Nitrospira has been widely reported as a complete aerobic ammonia‐oxidizing bacteria (comammox) (Gonzalez‐Martinez et al, 2016; Lawson & Lücker, 2018), and some Nitrospira , such as Nitrospira inopinata , have a relatively low affinity for nitrite, making the symbiotic association with anammox bacteria possible. Sustained nitrogen loss has been observed in a combination of Comammox Nitrospira and anammox bacteria, especially in low ammonia condition and sometimes in low DO condition (Gottshall et al, 2020; Roots et al, 2019; Shao & Wu, 2021). The dominant NOB genus in this case, as shown in the reference (Yuan et al, 2020), was Nitrospira , and its relative abundance in the suspended solids was 2 times higher in summer and 7 times higher in winter than the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Nitrospira in the suspended solids in this case acts as Comammox and cooperated with anammox bacteria attached on the carriers. Cooperation between Comammox and anammox bacteria were found both in a sequencing batch reactor for sludge digester liquor treatment (Wu et al, 2019) and in a continuous reactor for low‐strength ammonia‐containing wastewater treatment (Shao & Wu, 2021). van Kessel et al, (2015) reported that Comammox bacteria are capable to produce nitrite and cooperate with anammox for nitrogen removal.…”
Section: Discussionmentioning
confidence: 99%
“…Soil microcosms amended with high ammonia concentrations were enriched in AOB compared to those with lower ammonia concentrations where clade B comammox bacteria proliferated , He et al, 2021. Interestingly, in a lab-scale partial nitrification-anammox reactor operating with incrementally increased ammonia loadings, comammox bacteria initially dominated over strict AOB but its abundance significantly declined as loadings were further increased (Shao & Wu, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that clade-specific comammox bacterial niche, if applicable, may be arise from a combination of factors ranging from affinity to inhibition. Beyond clade specific traits, identifying the potential environmental and physiological factors driving the coexistence of comammox bacteria with canonical nitrifiers is also important to better understand comammox bacteria role in complex nitrifying communities (21)(22)(23)(24)(25)(26)(27)(28)(29). Comammox bacteria have been detected along with their canonical nitrifying counterparts in wastewater treatment plants (18,25,(30)(31)(32), drinking water systems (6,9,15,33,34) and soils (22,28,35,36) at varying abundances over a wide range of ammonium concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation